Correction: Zhao et al. Physics-Informed Deep Learning for Karst Spring Prediction: Integrating Variational Mode Decomposition and Long Short-Term Memory with Attention. Water 2025, 17, 2043 - Zhao, Liangjie; Fazi, Stefano; Luan, Song; Wang, Zhe; Li, Cheng; Fan, Yu; Yang, Yang (Water (Basel), 2025)
In the original publication [...]